Improving the public service delivery through client charter: a case study at Malacca Road Transport Department, UTC Malacca / Norhazimah Husain and Zaynor Ashiqin Abu Bakar - Husain, Norhazimah; Abu Bakar, Zaynor Ashiqin (Faculty of Administrative Science and Policy Studies, 2013)
The implementation of New Public Management (NPM) had transformed the public sector from being an engine of the country’s economic growth and development, to become a catalyst to the private sector and service provider to the public. In line with NPM’s underlying belief of superiority of private sector practices, a variety of contemporary management practices and philosophy such as the quality control circle and total quality management in the late 1980s, and performance-based appraisal in the remuneration system in early 1990s were implemented. Besides, civil servants are now encouraged and expected to behave like managers of business organizations in private sector. Similar to the private sector, civil servants are supposed to think and treat the citizens as customers of their services. As highlighted by Andrew (2012), transformation in government service delivery is taking place as governments are adopting innovative practices to bring changes in service delivery to the people. Public service includes wide range of services provided by public authorities such as advice and advocacy, education, and transportation. In line with this, governments are realizing that more efficient service delivery can significantly improve the value of public-sector which leads to customer satisfaction and service quality. Based on GTP Annual Report (2010), this courageous and extraordinary programme aimed to totally transform the way the Government worked so we could better serve the rakyat, regardless of race, religion or social status. In embracing change, we learnt how to listen more effectively, speak more openly, see things for what they really are, develop a positive course of action and deliver tangible solutions. Besides, in a highly competitive global environment, the public sector needs to focus on innovation to achieve transformational change. Referring to Siti Nabiha (2008) stated that the Malaysian public sector has undergone various transformations since the Independence. Therefore, public agencies were required to establish their respective client charter to represent their written commitment toward the provision of services to ensure customer satisfaction and service quality. Public services are the services provided by governments to the public. The need for services is free of charge but benefit all by the public stated by Tanya (2011). In this context, the public service delivery is the implementation of the services offered by governments and making sure that they reach all people and places that supposed to be. It is benefited to all public without have to pay for the service. According to Cabinet Secretariat (2009), Client’s Charter is a written declaration by a Government department that highlights the standards of service delivery that it promises to, availability of choice for consumers, channel for grievance restore and other related information. In other words, it is a set of commitments made by department regarding the standards of service which it delivers. As highlighted by Dato’ Dr. Tam Weng Wah, (2011), public service delivery always attributes customer satisfaction and expectation as the benchmark. Nick (2011) said that this implementation of client charter allows the public service to understand what their customers ‘value and how they perceived the service delivery. Thus, the needs of the customers can be recognized and further action can be taken to improve the public service delivery. Consequently, a better responsive service delivery system can be developed to improve the efficiency of the service delivery (Tanya, 2011). This research aims to understand the improvement of public service delivery through innovation.